High-throughput subcellular protein localization using cell arrays. (26th October 2005) - Hu, Y.-H.; Vanhecke, D.; Lehrach, H.; Janitz, M.
Abstract : Accomplishment of the human and mouse genome projects resulted in accumulation of extensive gene sequence information. However, the information about the biological functions of the identified genes remains a bottleneck of the post-genomic era. Hence, assays providing simple functional information, such as localization of the protein within the cell, can be very helpful in the elucidation of its function. Transfected cell arrays offer a robust platform for protein localization studies. Open reading frames of unknown genes can be linked to a His6 -tag or GFP (green fluorescent protein) reporter in expression vectors and subsequently transfected using the cell array. Cellular localization of the transfected proteins is detected either by specific anti-His-tag antibodies or directly by fluorescence of the GFP fusion protein and by counterstaining with organelle-specific dyes. The high throughput of the method in terms of information provided for every single experiment makes this approach superior to classical immunohistological methods for protein localization.